A Ceramic‐PVDF Composite Membrane with Modified Interfaces as an Ion‐Conducting Electrolyte for Solid‐State Lithium‐Ion Batteries Operating at Room Temperature. Issue 19 (24th July 2018) - Yu, Jing; Kwok, Stephen C. T.; Lu, Ziheng; Effat, Mohammed B.; Lyu, Yu‐Qi; Yuen, Matthew M. F.; Ciucci, Francesco
Abstract: Solid‐state batteries hold great promise because of their safety and high projected energy density. However, the sizeable interfacial resistance between the electrodes and the electrolyte of such batteries is a significant bottleneck in the development of this technology. In this work, we develop a Li6.4 La3 Zr1.4 Ta0.6 O12 (LLZTO) and polyvinylidene fluoride (PVDF) solid‐state composite membrane characterized by high conductivity, tensile strength, and flexibility as well as low impedance if interfacially modified by a minute amount of liquid electrolyte. A solid‐state lithium‐ion battery using this electrolyte with LiFePO4 and Li as electrodes delivers excellent rate capability and cycling stability at room temperature. In particular, the battery shows an initial discharge capacity of 155 mAh g −1 and, after 100 cycles at 1C, of 145 mAh g −1 . Even at 4C, the discharge capacity is 96 mAh g −1 . Our study suggests that the interfacially modified LLZTO‐PVDF membrane is a promising electrolyte for solid‐state lithium‐ion batteries. Abstract : Interface engineering : a highly conductive solid‐state membrane comprising LLZTO and PVDF is developed, showing high tensile strength, good flexibility, and low impedance when it is interfacially modified with 2 μL of liquid electrolyte. A solid‐state lithium‐ion battery using the LLZTO‐PVDF membrane as electrolyte delivers an excellent rate capability and cycling stability at room temperature, demonstrating its promising potential.